Intrapreneurial for Organizational Personnel in Airports - Charoensak, Panadda; Chamroonkul, Thatarot; Payon, Jirayu; Sakulkrit, Koranut (SOCIAL SCIENCES RESEARCH AND ACADEMIC JOURNAL, 2025)
This research used Mixed methods research integrating both qualitative and quantitative research methods. This research aimed to explore the conceptual framework of intrapreneurship development for airport personnel in Thailand. The research instruments included a content synthesis table derived from a review of relevant literature comprising 64 items and an evaluation form on the research framework titled "Model for Developing Intrapreneurship in Airport Personnel." The framework was assessed for its suitability by a panel of five experts. Data analysis was conducted using statistical methods, including mean (), standard deviation (S.D.), and content analysis The study revealed that the conceptual framework for the intrapreneurship development model for airport 1) Intrapreneurial consists of three key dimensions with a total of 16 characteristics, 1.1) The behavioral dimension includes 1.1.1) innovativeness 1.1.2) creativeness 1.1.3) proactiveness 1.14) opportunity recognition 1.1.5) risk-taking 1.1.6) tolerance of failure and 1.1.7) networking. 1.2) the attribute dimension includes 1.2.1) skills, 1.2.2) abilities 1.2.3) perception of their own capabilities 1.2.4) personal knowledge, and 1.2.5) experience. Lastly, 1.3) the attitudinal dimension includes 1.3.1) relationship to the organization 1.3.2) motivation 1.3.3) satisfaction, and 3.4) intention. 2) Airport services covers 9 dimensions: 2.1) safety standards 2.2) air traffic management 2.3) security management 2.4) passenger services 2.5) airport management 2.6) environment and sustainability 2.7) airport code designation 2.8) ground services, and 2.9) emergency management systems.